2023
DOI: 10.21203/rs.3.rs-2648939/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing Irt Properties of Different Likert Scale Lengths: a Case From Attitudinal Measurement on Physics Education Research

Abstract: Collapsing Likert scale length on attitudinal measurement toward learning and instruction can be an option by physics education researchers (PER) while interpreting categorical responses from participants. Psychometric evaluation of the different scale length, however, has inconclusive results to date. Item response theory (IRT) offers advanced information at the item level that has been approached in this simulation study to explore psychometric properties of five different Likert scale lengths. The total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They reported that ability estimates were good and stable under different conditions, and that the ability estimates became with higher accuracy when the sample size increased (500 and more). Other studies (Lee & Paek, 2014;Santoso et al, 2023) investigated the effect of different Likert scale response categories (3, 5, 7, 9, and 11 points) on psychometric properties within the IRT-GRM framework, and reported no differences among them as long as their items have good discrimination indices (>0.3). On the other side, Maydeu-Olivares et al (2009) reported that within IRT framework, increasing the number of response categories led to some improvement in precision of measurement, defined as the area under the TIF, however, it did not lead to increasing convergent validity, and it resulted in a worse fit of the model.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that ability estimates were good and stable under different conditions, and that the ability estimates became with higher accuracy when the sample size increased (500 and more). Other studies (Lee & Paek, 2014;Santoso et al, 2023) investigated the effect of different Likert scale response categories (3, 5, 7, 9, and 11 points) on psychometric properties within the IRT-GRM framework, and reported no differences among them as long as their items have good discrimination indices (>0.3). On the other side, Maydeu-Olivares et al (2009) reported that within IRT framework, increasing the number of response categories led to some improvement in precision of measurement, defined as the area under the TIF, however, it did not lead to increasing convergent validity, and it resulted in a worse fit of the model.…”
Section: Discussionmentioning
confidence: 99%